2021
DOI: 10.1007/s00484-021-02224-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the energy balance and CO2 flow under the influence of the seasonality of climatic elements in a mangrove ecosystem in Eastern Amazon

Abstract: An unprecedented study was carried out in a mangrove ecosystem in the northeastern coast of the Brazilian Amazon to understand the behavior of climatic elements in a year with the occurrence of El Niño (2015), associated with the seasonal function source/sink of CO2 by the ecosystem. Global radiation (Rg), net radiation (Rn), temperature, relative humidity, precipitation, horizontal wind speed and direction, as well as turbulent flows of sensible heat (H), latent heat (LE), and carbon (f_CO2) were recorded usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…This is important in the continuation of the mangrove forest as a C sink, as other Everglades studies have indicated wet season conditions during El Niño may drive increased CO 2 uptake and shorter dry seasons drive lower respiration (Malone et al., 2014). The length of the wet/dry season is also important in the timing of foliar abscission in Rhizophora as the onset of dry season promotes this strategy to reduce water stress (Fernandes et al., 2007; Freire et al., 2022). The interaction of salinity with hydroperiod length during these phases may also introduce an effect that we were not able to directly observe.…”
Section: Discussionmentioning
confidence: 99%
“…This is important in the continuation of the mangrove forest as a C sink, as other Everglades studies have indicated wet season conditions during El Niño may drive increased CO 2 uptake and shorter dry seasons drive lower respiration (Malone et al., 2014). The length of the wet/dry season is also important in the timing of foliar abscission in Rhizophora as the onset of dry season promotes this strategy to reduce water stress (Fernandes et al., 2007; Freire et al., 2022). The interaction of salinity with hydroperiod length during these phases may also introduce an effect that we were not able to directly observe.…”
Section: Discussionmentioning
confidence: 99%